PELAKSANAAN PELAYANAN PUBLIK DI BIDANG PENGAIRAN IRIGASI PERTANIAN DI KABUPATEN LOMBOK TIMUR DI TINJAU DARI UNDANG¬-UNDANG NOMOR 17 TAHUN 2019 TENTANG SUMBER DAYA AIR: THE IMPLEMENTATION OF PUBLIC SERVICES IN THE FIELD OF AGRICULTURAL IRRIGATION IRRIGATION IN EAST LOMBOK REGENCY - Lalu, Zulhadi (JURIDICA : Jurnal Fakultas Hukum Universitas Gunung Rinjani, 2021)
Irrigation facilities is one of the key factors in farming, especially for food crop farming, including rice. A smallscale irrigation system has an area of less than 500 hectares, and it is the backbone of family food security which in turn will lead to national food security. Damage irrigation system networks will threaten food production increase. In the future, irrigation infrastructure must be better managed so that agricultural sector can realize agricultural diversification, conserve wider irrigation system and maintain local wisdom and social capital in irrigation management. The objective of the paper is to analyze performance, problems and solutions of small irrigation systems in Indonesia, including small irrigation concepts and understanding, small irrigation performance and development, small irrigation development policies, factors affecting smallscale irrigation development, investments, and prospects. The paper also compares various performances, problems and solutions of small irrigation systems in other countries. Small scale irrigation performance is often better than large-scale irrigation, in the sense of water availability throughout the year and equitable water distribution for all service areas